Postharvest quality of ‘Baigent’ apples as a function of single and multiple preharvest spray aminoetoxivinylglycine and ethephon applications Qualidade pós-colheita de maçãs ‘Baigent’ em função da forma de aplicação de aminoetoxivinilglicina e etefom - Soethe C.* (2019)
© 2019, Sociedade Brasileira de Fruticultura. All rights reserved.The aim of this work was to evaluate the effect of single and multiple pre-harvest spray aminoethoxyvinylglycine (AVG) applications with or without ethephon, in ‘Baigent’ apple trees cultivated under anti-hail screen and harvesting date on fruit quality after storage. The experiment was conducted in a commercial orchard in the municipality of Vacaria/RS, in the 2014/15 and 2015/16 harvests. Treatments consisted of: control (plants sprayed with water); AVG (125 mg L-1, 30 days before the predicted harvest date; BPHD); ethephon (120 mg L-1, seven BPHD); AVG (62.5 mg L-1 + 62.5 mg L-1, 30 and 20 BPHD); AVG (62.5 mg L-1 + 62.5 mg L-1, 30 and 20 BPHD) + ethephon (120 mg L-1, seven BPHD). Fruits of all treatments were harvested at commercial harvest (harvest 1) and after 14 days (harvest 2). Fruits were evaluated after four months of cold storage (0.5 °C ± 0.2 °C and RH 92 ± 5%). The use of AVG, regardless of single or multiple applications, reduced ethylene production rate, skin yellowing, farinaceous pulp and senescent degeneration incidence and maintained higher pulp firmness values and pulp penetration and skin rupture strength. Ethephon provided fruits with higher farinaceous pulp incidence. Fruit treated with AVG, regardless of single or multiple application and combination with ethephon, presents better quality after cold storage.